2010
DOI: 10.1056/nejmoa1000367
|View full text |Cite|
|
Sign up to set email alerts
|

Body-Mass Index and Mortality among 1.46 Million White Adults

Abstract: BACKGROUND A high body-mass index (BMI, the weight in kilograms divided by the square of the height in meters) is associated with increased mortality from cardiovascular disease and certain cancers, but the precise relationship between BMI and all-cause mortality remains uncertain. METHODS We used Cox regression to estimate hazard ratios and 95% confidence intervals for an association between BMI and all-cause mortality, adjusting for age, study, physical activity, alcohol consumption, education, and marital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

90
1,405
16
60

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,043 publications
(1,571 citation statements)
references
References 36 publications
90
1,405
16
60
Order By: Relevance
“…Thus, smoking may significantly confound and attenuate the association between body weight and mortality 42. Consistent with previous studies,5 43 we found that body shape trajectory was more strongly associated with mortality among never smokers than among ever smokers. This difference seemed to be more striking in women than in men, which may be a result of the higher proportion of current smokers among women than among men (14% v 7%) in our cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, smoking may significantly confound and attenuate the association between body weight and mortality 42. Consistent with previous studies,5 43 we found that body shape trajectory was more strongly associated with mortality among never smokers than among ever smokers. This difference seemed to be more striking in women than in men, which may be a result of the higher proportion of current smokers among women than among men (14% v 7%) in our cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…We therefore used Cox proportional hazard models to calculate adjusted hazard ratios for all cause, cancer, and cardiovascular mortality with their 95% confidence intervals across the categories of BMI (<18.5, 18.5-22.4, 22.5-24.9, 25.0-27.4, 27.5-29.9, 30.0-34.9, 35.0-39.9, and ≥40) 23. We defined the BMI range of 22.5-24.9 as the reference category, as in previous studies 24. In our cohorts this was also the range of BMI associated with the lowest mortality (fig A in appendix 2).…”
Section: Methodsmentioning
confidence: 94%
“…Our study advances the existing literature by examining a cohort with extensive serial data collection—allowing careful control for chronic health conditions and sociodemographic factors. Our measures of baseline health status include not only measures of comorbidity but also previous hospital admissions, BMI,31 functional status,32 self rating of health,33 and measures of poverty (wealth and government assistance)34—all important predictors of long term mortality that have not been included in previous studies of late mortality after sepsis.…”
Section: Discussionmentioning
confidence: 99%